1979
DOI: 10.1161/01.res.44.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Human urinary and plasma kinins: relationship to sodium-retaining steroids and plasma renin activity.

Abstract: Sodium-retaining steroids increase urinary kallikrein but their effects on urinary kinins and plasma bradykinin are not known. Thirty-six normal subjects were studied during several different manipulations of dietary sodium and potassium or the administration of fludrocortisone or adrenocorticotropic hormone (ACTH). Urinary kallikrein and aldosterone excretion changed pari passu over a 30-fold range for kallikrein and an 80-fold range for aldosterone. Urinary kinin excretion was invariant. Plasma, bradykinin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
2

Year Published

1979
1979
1989
1989

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 27 publications
(51 reference statements)
4
28
2
Order By: Relevance
“…Although other studies have indicated a parallelism between changes of plasma bradykininl and those of plasma angiotensin II or renin activity in response to changes of' posture, salt depletion, or saline infusioni in normal subjects (12,17), in the present study, treatmlent of' normal subjects with indomethacin decreased PRA but did not affect plasma bradykinin (Table I). This difference in the response of' plasma bradykinin in normal subjects and in patients with Bartter's syndrome may be attrib)uted to the mtuch higher basal valtues of plasma bradykiniin and( PRA in the patients with Bartter's syndromiie (Fig.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Although other studies have indicated a parallelism between changes of plasma bradykininl and those of plasma angiotensin II or renin activity in response to changes of' posture, salt depletion, or saline infusioni in normal subjects (12,17), in the present study, treatmlent of' normal subjects with indomethacin decreased PRA but did not affect plasma bradykinin (Table I). This difference in the response of' plasma bradykinin in normal subjects and in patients with Bartter's syndrome may be attrib)uted to the mtuch higher basal valtues of plasma bradykiniin and( PRA in the patients with Bartter's syndromiie (Fig.…”
Section: Discussioncontrasting
confidence: 64%
“…Urinary kallikrein exeretioni is inereased in conditions in which soditum-retaining steroids are presenit in excess (14)(15)(16)(17). Consistent with this observation are the report by Lechi et al (45) and otir presenit findings that patients with Bartter's syndrome excrete more kallikreini than normiial subjects.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…17 Thus, because of its many actions, SQ20,881 is not simply a selective inhibitor of the renin-angiotensin system as is the antagonist and partial agonist, [Sar 1 , Ala']-angiotensin II. The latter had no significant depressor effect in normal-renin hypertensives, 18 but SQ20,881 significantly decreased diastolic pressure in more than 90% of normal-renin hypertensives. 17 Because of the proposed multiple actions of converting enzyme inhibition we investigated the extent to which changes in levels of kinins and prostaglandins, as well as angiotensin II, might contribute to the depressor effects of SQ20.881 in patients with normal and low-renin hypertension.…”
mentioning
confidence: 77%
“…Dr. Chao is a Research Career Development Awardee of the National Heart, Lung, and Blood Instittite. Receivedfor publication 24 September 1979 and in revised fori 15 February 1980. ing effects upon sodium and water transport across membranes (1,2). In humans and rats, sodium-retaining steroids or maneuvers which increase aldosterone activity, such as reduced dietary sodium or increased dietary potassium increase renal and urinary kallikrein activity; whereas spironolactone reduces it (3)(4)(5)(6)(7)(8)(9). Kallikrein excretion is elevated in primary aldosteronism or Bartter's syndrome (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%